Empatia e reciprocidade em ratos Wistar: um paradigma para avaliar comportamento pró-social - Silva, Phiética Raíssa Rodrigues da (2016)
Prosocial behavior refers to any actions that are intended to benefit others, regardless of benefits to the actor in the process. This is a very broad term that includes many subcomponents, such as cooperation, mutualism, altruism and helping. Cooperation often brings a cost for the cooperator, resulting in a fitness decrease. Therefore, cooperation seems contradictory to the theory of natural selection. However, mechanisms that promote the development of cooperation were selected, such as kin selection, direct reciprocity and generalized reciprocity. Behind prosocial behavior can be a motivating emotional component, such as empathy. Empathy is the capacity to experience emotional reactions when observing the experience of others (emotional empathy), sharing their emotional state, and being able to adopt their point of view (cognitive empathy). There is still no established animal model for the study of empathy as motivating prosocial behavior, in its various aspects. Thus, we use a protocol that proposes to assess empathy and prosocial behavior in rats (Bartal et al., 2011) to verify its reproducibility and try to understand aspects such as helping and cooperation (direct and generalized reciprocity) and the main motivation for these behaviors. The helping behavior was evaluated through the opening of the door of a restraining box, releasing a trapped cagemate. Future retribution in the task was the parameter used to investigate reciprocity to a familiar (direct) or unfamiliar (generalized) animal. The rats received no training or reward for the task. We reproduced the results of the original protocol and verified the presence of reciprocity, but could not discriminate between direct and generalized reciprocity. We identified other factors associated with the door opening. We have seen that the animals kept opening the door when tested with an empty restraining box, after learning how to open the door. We also saw that the “opener” rats entered the box after opening and stayed there most of the time during the test. When rats were previously submitted to the empty box and after that to the conspecific box there was no opening in any of the circumstances, indicating a possible effect of habit on the behavior. Therefore, it is necessary to investigate other factors that may be involved in door opening before considering the use of the paradigm currently used for investigation of mechanisms related to empathy and prosocial behavior.